Propuesta de mejora para el laboratorio de control de calidad bajo el cumplimiento de requisitos según la norma ISO/IEC 17025 en la empresa Fabril FAME S.A - Olmedo Velasco, Yolanda Soraya (2011)
The following proposal for improvement in the quality control laboratory, FAME S.A. Manufacturing Company S.A., have conducted an analysis of nonconformities presented in the final report of the audit by the accreditation department of Ecuador OAE for the laboratory designation process. In this proposal, it includes an action plan for the lifting of non-conformities that were analyzed according to standard of ISO INEN IEC 17025:2005. “General requirements for the competence of testing laboratories and calibration” also checked the reasons for such non-compliance occurred. Throughout the thesis, it shows how the quality control laboratory has improved its facilities, procedures, personnel, and appropriate equipment in order to improve the department and meet the requirements for the designation of the laboratory…